(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the role of philosophy in shaping human spiritual perfection and ensuring social stability. In the context of modern society, philosophical thinking serves as a key tool for reinforcing moral values, fostering spiritual development, and promoting harmonious functioning of the community. The study highlights the connection between human spiritual growth and societal stability, emphasizing the relevance of this process in contemporary social settings.